Clinical Evaluation of Bulk-Fill Flowable Composite versus Traditional Nano-Hybrid Composites in Posterior Teeth - Pervez, Jazib; Ghani, Bushra; Ashraf, Usman; Ahmed, Farrukh; Ishaq, Bismah; Aziz, Samiya (Journal of Postgraduate Medical Institute, 2024)
Objective: To evaluate and compare the clinical performance of bulk-fill flowable composites and conventional nano-hybrid composites to restore posterior teeth. Methodology: A Randomized controlled trial was conducted at Bakhtawar Amin Dental College, Multan, from July 2022 to Jun 2023. A total of 140 subjects were included in the study, with 70 assigned to the bulk-fill flowable composite group (Group A) and 70 to the traditional composite group (Group B). The restorations were assessed for retention, marginal integrity, and postoperative sensitivity over a 3-month follow-up period. Data was analyzed with SPSS version 26.0. Results: 28 teeth were dropped out of the study, leaving 112 teeth. No significant differences were found between the two groups (A and B) in restoration outcomes according to USPHS criteria (taking p > 0.05 as significant), with chi-square values of 1.46 (p = 0.48), 2.53 (p = 0.28), and 3.77 (p = 0.15) for restoration retention, marginal integrity, and postoperative sensitivity, respectively. Conclusion: Both bulk-fill flowable composite and traditional composite materials in posterior teeth restorations show favorable clinical performance in terms of restoration retention and marginal integrity with minimal post-operative sensitivity. However, further research is needed to assess the long-term performance of these materials.